11C-radiolabeled aptamer for imaging of tumors and metastases using positron emission tomography- computed tomography - Anastasia V. Ozerskaya; Tatiana N. Zamay; Olga S. Kolovskaya; Nikolay A. Tokarev; Kirill V. Belugin; Natalia G. Chanchikova; Oleg N. Badmaev; Galina S. Zamay; Irina A. Shchugoreva; Roman V. Moryachkov; Vladimir N. Zabluda; Vladimir A. Khorzhevskii; et al. (Elsevier, 2021)
Identification of primary tumors and metastasis sites is an essential step in cancer diagnostics and the following treatment. Positron emission tomography-computed tomography (PET/CT) is one of the most reliable methods for scanning the whole organism for malignancies. In this work, we synthesized an 11C-labeled oligonucleotide primer and hybridized it to an anti-cancer DNA aptamer. The 11C-aptamer was applied for in vivo imaging of Ehrlich ascites carcinoma and its metastases in mice using PET/CT. The imaging experiments with the 11C-aptamer determined very small primary and secondary tumors of 3 mm2 and less. We also compared 11C imaging with the standard radiotracer, 2-deoxy-2-[fluorine-18]fluoro-D-glucose (18F-FDG), and found better selectivity of the 11C-aptamer to metastatic lesions in the metabolically active organs than 18F-FDG. 11C radionuclide with an ultra-short (20.38 min) half-life is considered safest for PET/CT imaging and does not cause false-positive results in heart imaging. Its combination with aptamers gives us high-specificity and high-contrast imaging of cancer cells and can be applied for PET/CT-guided drug delivery in cancer therapies.